The Demand for and Supply of Accounting Theories: The Market for Excuses. - Watts, Ross L.; Zimmerman, Jerold L. (The Accounting Review, 1979)
Abstract ABSTRACT: This paper addresses the questions of why accounting theories are predominantly normative and why no single theory is generally accepted. Accounting theories are analyzed as economic goods, produced in response to the demand for theories. The nature of the demand is examined, first in an unregulated, then in a regulated economy. Government regulation creates incentives for individuals to lobby on proposed accounting procedures, and accounting theories are useful justifications in the political lobbying. Further, government intervention produces a demand for a variety of theories, because each group affected by an accounting change demands a theory that supports its position. The diversity of positions prevents general agreement on a theory of accounting, and accounting theories are normative because they are used as excuses for political action (i.e., the political process creates a demand for theories which prescribe, rather than describe, the world). The implications of the authors' theory for the changes in the accounting literature as a result of major changes in the institutional environment are compared with observed phenomena.